2016
DOI: 10.1111/bcpt.12635
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Action and Toxicity of the Mycotoxin Alternariol: A Review

Abstract: The mycotoxin alternariol (AOH) is produced by Alternaria fungi. It occurs naturally in foodstuffs and is frequently found as contaminant in fruit and grain products. Most information regarding AOH toxicity and the potential mechanisms involved comes from in vitro studies, as only very limited in vivo studies have been performed. AOH forms reactive oxygen species (ROS) and interacts with DNA topoisomerase, thereby generating both single (SSB)-and double-strand DNA beaks (DSB). This triggers various DNA damage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 55 publications
(120 reference statements)
0
59
0
Order By: Relevance
“…The most prevalent Alternaria toxin found in grain is alternariol (AOH). Several in vitro studies have reported that AOH induces DNAdamage (Pfeiffer et al, 2007;Solhaug et al, 2012), which is linked to its ability to act as a topoisomerase poison (Fehr et al, 2009;Solhaug et al, 2016). Cellular effects such as generation of ROS, cell cycle arrest, appearance of abnormal nuclei, autophagy, senescence (Solhaug et al, 2012(Solhaug et al, , 2013(Solhaug et al, , 2014, differentiation, secretion of cytokines and estrogenic potential (Frizzell et al, 2013) has also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The most prevalent Alternaria toxin found in grain is alternariol (AOH). Several in vitro studies have reported that AOH induces DNAdamage (Pfeiffer et al, 2007;Solhaug et al, 2012), which is linked to its ability to act as a topoisomerase poison (Fehr et al, 2009;Solhaug et al, 2016). Cellular effects such as generation of ROS, cell cycle arrest, appearance of abnormal nuclei, autophagy, senescence (Solhaug et al, 2012(Solhaug et al, , 2013(Solhaug et al, , 2014, differentiation, secretion of cytokines and estrogenic potential (Frizzell et al, 2013) has also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Effects can be often observed in the 5–10 μM range suggesting low acute toxicity [19]. Alternariol-9-methyl ether ( 3 ) exhibited antibacterial activities with IC 50 values ranging from 59 nM to 141 nM.…”
Section: Discussionmentioning
confidence: 99%
“…Tenuazonic acid has been reported to be acutely toxic for several animals such as mice, chickens, and dogs, and has been associated with human hematological disorders like onyalai . Alternariol and AME are mutagenic and genotoxic in bacterial and mammalian cells in vitro . The presence in food of these two toxins has been associated with high levels of human oesophageal cancer in China .…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] Alternariol and AME are mutagenic and genotoxic in bacterial and mammalian cells in vitro. 5,10 The presence in food of these two toxins has been associated with high levels of human oesophageal cancer in China. 8,11 Even though there are still no international regulations for any of the Alternaria mycotoxins in food and feed, the European Food Safety Authority (EFSA) recently highlighted that the major contribution of Alternaria spp.…”
Section: Introductionmentioning
confidence: 99%